2016
DOI: 10.3354/aei00178
|View full text |Cite
|
Sign up to set email alerts
|

Not too slow, not too fast: water currents affect group structure, aggression and welfare in post-smolt Atlantic salmon Salmo salar

Abstract: Increased swimming speed of Atlantic salmon is generally considered an improvement to welfare under aquaculture settings, as group structure is improved and agonistic behaviour reduced. As such, establishing fish farms in exposed areas with fast water current velocities should be favourable. However, at some locations, velocities exceed what is known as preferable for salmonids, and this may compromise fish welfare. In this study, behaviour and fin erosion were observed on post-smolt salmon stocked at 39 kg m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…In salmonids, aggressive attacks, demonstrated to mainly aim for the dorsal and/or caudal fins (Abbott and Dill, 1985;Bosakowski and Wagner, 1994a;Moutou et al, 1998;Maclean et al, 2000), could be reduced by increased swimming activity due to an increased flow velocity (Jobling et al, 1993;Davison, 1997). From a welfare perspective, studies on salmonids indicate that a velocity is considered ideal when balanced between territorial behaviour and individual interactions at too low velocities, and collisions with tank walls or other individuals at too high velocities (Solstorm et al, 2016). Velocity was not measured in this study however a comparably higher velocity is indicated by a high water supply and shorter total water exchange duration.…”
Section: Feeding Frequency Stocking Density and Water Velocity In Rel...mentioning
confidence: 99%
“…In salmonids, aggressive attacks, demonstrated to mainly aim for the dorsal and/or caudal fins (Abbott and Dill, 1985;Bosakowski and Wagner, 1994a;Moutou et al, 1998;Maclean et al, 2000), could be reduced by increased swimming activity due to an increased flow velocity (Jobling et al, 1993;Davison, 1997). From a welfare perspective, studies on salmonids indicate that a velocity is considered ideal when balanced between territorial behaviour and individual interactions at too low velocities, and collisions with tank walls or other individuals at too high velocities (Solstorm et al, 2016). Velocity was not measured in this study however a comparably higher velocity is indicated by a high water supply and shorter total water exchange duration.…”
Section: Feeding Frequency Stocking Density and Water Velocity In Rel...mentioning
confidence: 99%
“…Farmed fish are reared in high densities and agonistic behaviour has been observed in several species (Barreto, Boscolo & Gonçalves‐de‐Freitas, ; Fernö & Holm, ; Jobling, ; Solstorm et al., ). Aggressive individuals should be expected to influence the baseline behaviour and stress level of subordinate fish and could thereby interfere with the processes of habituation and conditioning.…”
Section: Introductionmentioning
confidence: 99%
“…Swimming behaviour of fish in the Preline was quite different than in the open pen (Supporting Information Video S1). In Preline, fish swam against the current, showing fewer interactions and less aggressive behaviour, as it has been previously observed in fish exposed to constant currents (Christiansen et al ., ; Jobling et al ., ; Solstorm et al ., ). In calm waters, salmonids tend to form dominant hierarchies, inducing differences in size within the fish population (Adams et al ., ; Brännäs, ; Winberg et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Aggressive behaviour can produce lesions, which can in turn facilitate infections. Furthermore, high aggression can lead to increased spontaneous activity with higher energetic costs and increment of the feed conversion ratio of the population (Christiansen et al, 1991;Solstorm et al, 2016).…”
Section: Heart Gene Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation